A Novel Combinatorial Approach to the Ferroelectric Properties in HfxZr1−xO2 Deposited by Atomic Layer Deposition. Issue 5 (1st April 2021) - Jung, Yong Chan; Mohan, Jaidah; Hwang, Su Min; Kim, Jin-Hyun; Le, Dan N.; Sahota, Akshay; Kim, Namhoon; Hernandez-Arriaga, Heber; Veyan, Jean-Francois; Kim, Harrison Sejoon; Kim, Si Joon; Choi, Rino; et al.
Abstract : Since HfO2 ‐based ferroelectric films were reported in 2011, several doping/alloying elements have been introduced to secure interesting ferroelectric/antiferroelectric properties of Hf‐based fluorite‐structured thin films. Using a conventional approach by atomic layer deposition (ALD), an enormous number of experiments would be required to reveal the compositional effects of doping/alloying components in ternary and quaternary systems. Therefore, for a comprehensive study of the ferroelectric properties of Hf x Zr1− x O2, a novel combinatorial ALD technique that enables the fabrication of multicomponent films with a different composition ratio and thickness via saturated/non‐saturated ALD without changing the supercycle of each material is reported. The gradient of the amount of HfO2 over a 100 mm substrate is achieved using a lower Hf‐precursor temperature that results in an insufficient Hf‐precursor dose for saturated deposition. Systematic study on the Hf x Zr1− x O2 combinatorial library is carried out by spectroscopic ellipsometry, X‐ray photoelectron spectroscopy, and X‐ray diffraction. Furthermore, TiN/Hf x Zr1− x O2 /TiN capacitors are fabricated to measure the remnant polarization. The obtained results clearly show the ferroelectric–antiferroelectric transition according to continuous composition change instead of discrete research. Therefore, a highly productive method for studying ferroelectricity changes in terms of a doping and a composition of HfO2 ‐based ferroelectric thin films through a novel ALD combinatorial approach is proposed. Abstract : A novel combinatorial approach to investigate the ferroelectricity of Hf x Zr1− x O2 thin films via a saturated/non‐saturated atomic layer deposition (ALD) technique is proposed. Detailed observation of continuous variation of the ferroelectric–antiferroelectric transition is successfully applied. It is possible to achieve a higher efficiency method for studying ferroelectricity change in terms of the doping and composition of HfO2 ‐based ferroelectric thin films through this combinatorial approach.